Local hyperthermia combined with CTLA-4 blockade induces both local and abscopal effects in a murine breast cancer model. (1st January 2021) - Ibuki, Yoriko; Takahashi, Yutaka; Tamari, Keisuke; Minami, Kazumasa; Seo, Yuji; Isohashi, Fumiaki; Koizumi, Masahiko; Ogawa, Kazuhiko
Abstract: Purpose: To evaluate the antitumor efficacy in local and distant tumors induced by local hyperthermia with CTLA-4 blockade Methods: A mouse breast cancer cell line was inoculated into both sides of the legs of mice. The mice were treated with three administrations of CTLA-4 blockade, a single application of local hyperthermia (42.5 °C for 20 min) to the tumor on one side of the leg, or the combination of the two. Tumor growth in locally heated tumors (HT tumors) and unheated distant tumors (UnHT tumors) and overall survival were evaluated. Results: In the combination group, tumor volume significantly decreased for both HT and UnHT tumors compared with the tumors in the untreated and local hyperthermia monotherapy groups. Remarkable efficacy was only observed in the combination therapy group, in which 7 of 18 mice responded to HT and UnHT tumors, with significant prolonged overall survival. Conclusions: Combination therapy enhanced the antitumor response not only in HT tumors but also in UnHT tumors and prolonged overall survival.